NEITHER NATIONAL, NOR REALLY ARTISTIC, BUT BY NO MEANS NEGLIGIBLE: THE POPULAR MUSIC TO MARIO DE ANDRADE’S EARS - André Domingues dos Santos (Gragoatá, 2015)
It remains a very negative view on critics about the relationship of the modernists, especially Mário de Andrade, with the Popular Music. This study aims to review the matter in the light of Mario’s writings, exploring both internal dialogues of modernism, critical production and artistic practice (in this case, commenting an obscure partnership between Andrade and the pianist Marcelo Tupinambá, "Canção marinha"). Far less than a mechanical refusal, the author creates a complex elective operation of elements for exaltation or rejection in the works of artists of Popular Music.